Expanding the boundaries of museum studies: Popular education through engagement with hidden histories of organising and activism. Issue 2 (November 2016) - Toth, Emese R; Guttman, Sandy; Kimura, Andie; Quinn, Therese
This article shares a descriptive case study of a popular education project entitled Alternative Tours UIC (ALTourUIC) that took place during a graduate course in the Museum and Exhibition Studies Programme at University of Illinois at Chicago. The educational activities created by the students included a map locating historically rich areas of campus, guided and self-guided tours, and social media spaces inviting participants to contribute stories of campus-based activism. The aims were to make visible marginalised and suppressed histories of activism and organising by members of the campus community at University of Illinois at Chicago. Importantly, this article offers a model of popular education that we recommend be taken up by museums to create greater awareness of frequently unknown and ignored histories and actively engage students in critical learning and investigation.